How to Reflect on 20th Century Man Facing Dramatic Situations and Hard Choices? - Švedas, Aurimas (Lietuvos istorijos studijos, 2023)
This article seeks to answer the question what ideas formed in the field of history theory can help develop a new interpretation of 20th century history, people facing difficult situations, the decisions they made, and, finally, traumatic individual and collective memory. The turbulent 20th century history and the memories about it is controversial; therefore, when contemporary Lithuanian society endeavors to discuss certain events, phenomena, and personalities and tries to come to a consensus on their immortalization – disagreements inevitably arise. In the process of research, it transpired that in contemporary historiography concerning the purpose and meaning of a historian’s work, as well as the responsibility to society of researchers of the past, several points are emphasized: (1) in the 21st century, historians have to find a new way of dealing with the complex issues of history; (2) scholars must recognize a responsibility for people who lived in the past and live the present, as well as to strive to show in the present perspective the fates of those who lived in the past; (3) the study of the past should contribute to the development of “intercultural competencies” which contemporary man lacks and which help him to understand The Other (past and present man); (4) to achieve these goals, historians need to transform their discipline into a “profession of understanding” that promotes inquisitiveness and openness to the world; (5) researchers of the past, when confronted with attempts to turn them into politicians or judges, have to leave the past open to new questions and interpretations; (6) those who study the past must engage in theoretical (self-)reflection that is necessary to perform the function of a critic that is so vital to society; and (7) historians need to think about the importance of the present dimension confronting complex historical issues. Historians work with collective memory to address the issues of self-awareness in time which face society. Researchers into the past also seek to initiate a dialogue between the people of the past and present. The conduct of the dialogue and its quality depend to a large extent on the level of the empathy that has been developed. Introducing empathy as a method for exploring knowledge about history and the present, this article draws on the ideas of George R. Collingwood, a British historian, archaeologist, and philosopher.
Keywords: 20th century history; evil; empathy; theory of history